Situation Report: Hungary, 8 June 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Wage Differentiation Causes Uproar in the Schools Implementation of Nazi Indemnities' Agreement Budapest International Fair 1971 Development of Production and Productivity during the Third Five-Year Plan (1966-1970) Private Artisans in Budapest TV "Forum" - Viewers Raise Questions Leaders, Specialists, and Well-Known Journalists Answer Coverage of the NATO Conference in Lisbon "Refloated" Agricultural Co-operatives in Difficulty The Harvest Is Coming, While Difficulties Linger on